Legal Protection of Creditors with Rejected Claims under Debt Payment Suspension Framework - Anis Mashdurohatun; Jamaslin James Purba; Edi Purwanto; Gunarto Gunarto; Henning Glaser (Lembaga Contrarius Indonesia, 2026)
The legal framework governing the Suspension of Debt Payment Obligations facilitates equitable debt restructuring; however, it fails to provide adequate protection for creditors whose claims debtors reject because it lacks a clear dispute resolution mechanism that ensures legal certainty and upholds justice. This study applies a normative juridical method through statutory, conceptual, and analytical approaches. It constructs its theoretical foundation upon principles of justice, the normative values of Pancasila, and progressive legal thought in order to evaluate both normative coherence and substantive fairness. The results demonstrate that first, the current system fails to provide adequate legal protection for creditors because it does not establish a renvoi mechanism to resolve disputed claims within the process, which creates uncertainty in claim verification. Second, the system depends on the discretionary authority of the supervisory judge, which does not consistently produce fair and predictable outcomes for creditors. Third, the regulatory framework prioritizes procedural efficiency over the realization of substantive justice, thereby weakening the protection of creditor rights and indicating the need for legal reconstruction to develop a more balanced framework that ensures legal certainty, fairness, and effective dispute resolution.